Salinomycin inhibits cholangiocarcinoma growth by inhibition of autophagic flux - Klose, Johannes; Schmidt, Thomas; Schneider, Martin; Ulrich, Alexis (OncoTarget, 2018)
Oncotarget | https://doi.org/10.18632/oncotarget.23339 Johannes Klose, Engin Guerlevik, Tina Trostel, Florian Kühnel, Thomas Schmidt, Martin Schneider, Alexis Ulrich